A fuel cell catalyst and a method for preparing the same

CN121260824BActive Publication Date: 2026-10-27GUANGDONG ELECTRIC POWER SCI RES INST ENERGY TECH CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202511395397.3
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2025-09-28
Publication Date
2026-10-27
Estimated Expiration
2045-09-28

AI Technical Summary

Technical Problem

目前,燃料电池催化剂通常使用纯铂(Pt)等贵金属作为活性组分,将其负载于碳载体之上,这些贵金属资源稀缺且价格高昂,同时也导致催化剂成本较高

Benefits of technology

[0032]本发明制备方法通过使用易升华的碘化铵(NH4I)与经石墨化热处理的导电炭黑的均匀混合,在热处理过程中碘化铵升华至石墨化导电炭黑表面实现原位掺杂,形成碘掺杂耐电压载体,随后在碘掺杂耐电压载体负载Pt,通过引入碘可以调控Pt的电子结构,增加碘和铂的相互作用,能够提高燃料电池工作电压和催化剂工作寿命。此外,本发明制备方法简单、环保,具有广泛的应用前景。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN121260824B_ABST
    Figure CN121260824B_ABST
Patent Text Reader

Abstract

The present application relates to a kind of fuel cell catalyst and its preparation method, belong to fuel cell technical field.The preparation method of fuel cell catalyst provided by the present application includes the following steps: (1) the heat treatment of conductive carbon black is obtained graphitized conductive carbon black;(2) ammonium iodide is mixed with the graphitized conductive carbon black obtained in step (1), obtain mixed powder, then the obtained mixed powder is calcined, obtain iodine-doped carrier;(3) the iodine-doped carrier obtained in step (2) is immersed in platinum salt solution, dry, heat treatment in reducing atmosphere, the fuel cell catalyst is obtained.The preparation method of the present application is by using the uniform mixing of easy sublimation ammonium iodide and graphitized heat-treated conductive carbon black, in the process of heat treatment, ammonium iodide sublimes to the surface of graphitized conductive carbon black to realize in-situ doping, form iodine-doped voltage-resistant carrier, then load Pt on the iodine-doped voltage-resistant carrier, the fuel cell catalyst with high stability and excellent electrochemical performance is obtained.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of fuel cell technology, specifically relating to a fuel cell catalyst and its preparation method. Background Technology

[0002] With increasing global emphasis on clean energy and sustainable development, the hydrogen energy and fuel cell industry has experienced rapid growth. Fuel cells, as efficient and clean energy conversion devices, have broad application prospects in transportation, power, and industry. However, the operating efficiency of existing fuel cells falls significantly short of theoretical values, making it difficult for their operating costs (hydrogen consumption) to meet commercialization needs. One significant reason for this is the excessive polarization loss caused by insufficient catalyst activity. Therefore, the research and application of fuel cell catalysts have become a key factor driving the development of the hydrogen energy and fuel cell industry.

[0003] At the anode and cathode of a fuel cell, catalysts can significantly reduce the activation energy of electrochemical reactions, thereby accelerating the reaction process and improving the cell's output power and efficiency. Particularly in the oxygen reduction reaction (ORR) at the cathode, due to the complexity and slowness of this process, the addition of catalysts can significantly increase the cathode reaction rate, thus improving the overall performance of the fuel cell. Currently, fuel cell catalysts typically use precious metals such as pure platinum (Pt) as active components, supported on carbon carriers. These precious metal resources are scarce and expensive, leading to high catalyst costs.

[0004] Therefore, developing a low-cost and high-performance fuel cell catalyst is of great significance. Summary of the Invention

[0005] The purpose of this invention is to overcome the problems existing in the prior art and to provide a fuel cell catalyst and its preparation method.

[0006] This invention is achieved through the following technical solution:

[0007] In a first aspect, the present invention provides a method for preparing a fuel cell catalyst, comprising the following steps:

[0008] (1) Heat treatment is performed on conductive carbon black to obtain graphitized conductive carbon black;

[0009] (2) Mix ammonium iodide with the graphitized conductive carbon black obtained in step (1) to obtain a mixed powder, and then calcine the mixed powder to obtain an iodine-doped carrier.

[0010] (3) The iodine-doped support obtained in step (2) is impregnated in a platinum salt solution, dried, and heat-treated in a reducing atmosphere to obtain the fuel cell catalyst.

[0011] The preparation method of this invention involves uniformly mixing easily sublimable ammonium iodide (NH4I) with graphitized conductive carbon black. During the heat treatment process, ammonium iodide sublimates to the surface of the graphitized conductive carbon black to achieve in-situ doping, forming an iodine-doped voltage-resistant support. Subsequently, Pt is loaded onto the iodine-doped voltage-resistant support to obtain a fuel cell catalyst with high stability and excellent electrochemical performance.

[0012] This invention employs vapor deposition to prepare the iodine-doped support. Leveraging the readily sublimable nature of ammonium iodide, it diffuses as a gaseous dopant phase onto the surface of the conductive carbon black during the heat treatment process, where it is partially adsorbed, thus modifying the surface of the conductive carbon black. No organic solvents are used in this process, making it environmentally friendly. Furthermore, the vapor-deposited iodine-doped phase indicates that gas can penetrate and fully contact with oxygen in the subsequent oxygen reduction reaction, maximizing the utilization of active sites.

[0013] This invention introduces iodine, a highly electronegative element with a large radius, which helps to regulate the electronic structure of platinum (Pt), giving it a binding energy that matches the oxygen-containing intermediates in the oxygen reduction reaction (ORR), thereby lowering the OCR energy barrier and accelerating the OCR catalytic reaction. Simultaneously, iodine doping creates a strong interaction between the support and Pt, effectively mitigating sintering and agglomeration of Pt during the heat treatment process, reducing platinum particle size, increasing the electrochemical active area, and reducing activation polarization losses in the high-efficiency operating region (high operating voltage). This allows for a suitable increase in the fuel cell operating voltage to improve power generation efficiency. Furthermore, the strong interaction between the support and platinum through iodine doping also inhibits platinum particle migration and loss during operation, improving catalyst lifetime.

[0014] Furthermore, the graphitization heat treatment of the conductive carbon black support by the preparation method of the present invention is beneficial to improving the support's resistance to high-voltage oxidation and corrosion, enhancing the durability of the fuel cell catalyst support under high-efficiency conditions (high operating voltage), and ensuring that the fuel cell can operate stably under high-efficiency conditions.

[0015] Optionally, in step (1), the conductive carbon black includes at least one of Vulcan XC-72R, Ketjen Black, and BP2000.

[0016] Preferably, in step (1), the heat treatment temperature is 1300℃-2200℃ and the time is 2h-5h.

[0017] Preferably, in step (2), the mass ratio of ammonium iodide to graphitized conductive carbon black is 1:(10-30).

[0018] More preferably, in step (2), the mass ratio of the iodized salt to the graphitized conductive carbon black is 1:(15-25).

[0019] Preferably, in step (2), the calcination is carried out in an inert atmosphere.

[0020] Preferably, in step (2), the calcination temperature is 700℃-1000℃, the time is 1h-3h, and the heating rate is 2℃ / min-6℃ / min.

[0021] Preferably, in step (2), the mixing is performed by grinding, and the grinding time is 20 min to 40 min.

[0022] Preferably, in step (3), the mass ratio of the iodine-doped carrier to the platinum salt is (2-6):1.

[0023] Preferably, in step (3), the platinum salt includes platinum nitrate.

[0024] Preferably, in step (3), the solvent of the platinum salt solution is water and ethanol; optionally, the volume ratio of water to ethanol is 3:7.

[0025] Preferably, in step (3), the impregnation is carried out under stirring, the stirring rate is 200rpm-400rpm, and the time is 12h-24h.

[0026] Preferably, in step (3), the drying temperature is 40℃-80℃.

[0027] Preferably, in step (3), the heat treatment temperature is 120℃-240℃, the time is 1h-3h, and the heating rate is 1℃ / min-5℃ / min.

[0028] Preferably, in step (3), the reducing atmosphere is a mixture of hydrogen and argon; optionally, the volume ratio of hydrogen to argon is 5:95.

[0029] Secondly, the present invention provides a fuel cell catalyst prepared by the method for preparing the fuel cell catalyst.

[0030] The fuel cell catalyst prepared by the method of this invention can regulate the electronic structure of Pt by introducing iodine, increase the interaction between iodine and platinum, and make it have a more suitable binding energy with oxygen reduction reaction intermediates. It also has good resistance to thermal sintering and electrochemical sintering loss. When applied to fuel cells, it can effectively improve the performance of fuel cells.

[0031] The present invention has the following beneficial effects:

[0032] The preparation method of this invention involves uniformly mixing easily sublimable ammonium iodide (NH4I) with graphitized heat-treated conductive carbon black. During the heat treatment process, ammonium iodide sublimates to the surface of the graphitized conductive carbon black, achieving in-situ doping and forming an iodine-doped voltage-resistant carrier. Subsequently, Pt is loaded onto the iodine-doped voltage-resistant carrier. By introducing iodine, the electronic structure of Pt can be modulated, increasing the interaction between iodine and platinum, thereby improving the operating voltage of the fuel cell and the catalyst's lifespan. Furthermore, the preparation method of this invention is simple, environmentally friendly, and has broad application prospects. Attached Figure Description

[0033] Figure 1 The image shows the morphology of the fuel cell catalyst prepared in Example 1.

[0034] Figure 2 Linear sweep voltammetry curves of the fuel cell catalysts prepared in Examples 1-2 and Comparative Examples 1-2 are shown. Detailed Implementation

[0035] To better illustrate the objectives, technical solutions, and advantages of this invention, the invention will be further described below with reference to specific embodiments. Those skilled in the art should understand that the specific embodiments described herein are merely illustrative of the invention and are not intended to limit the invention.

[0036] Unless otherwise specified, the experimental methods used in the examples are conventional methods; the materials and reagents used are commercially available unless otherwise specified.

[0037] Example 1

[0038] A method for preparing a fuel cell catalyst includes the following steps:

[0039] (1) Conductive carbon black Vulcan XC-72R was subjected to high-temperature graphitization heat treatment at a temperature of 1800℃ and a holding time of 3h to obtain graphitized conductive carbon black (GC).

[0040] (2) Mix ammonium iodide and graphitized conductive carbon black obtained in step (1) in a mortar at a mass ratio of 1:20 for 40 min to obtain mixed powder. Place the mixed powder in a tube furnace, remove the air in the tube furnace, and heat-treat it in an inert atmosphere at a constant heating rate of 3℃ / min to 800℃ for 2 h to obtain iodine-doped carrier (I-GC).

[0041] (3) The iodine-doped support obtained in step (2) is dispersed with platinum nitrate at a mass ratio of 3.5:1 in a 30% water-70% ethanol solution and thoroughly stirred and mixed for 20 hours. The mixture is dried at 60°C and then heat-treated in a tubular atmosphere furnace under 5% hydrogen / 95% argon conditions at 3°C / min to 180°C for 1.5 hours to obtain the fuel cell catalyst (Pt / I-GC).

[0042] Example 2

[0043] A method for preparing a fuel cell catalyst includes the following steps:

[0044] (1) Conductive carbon black BP2000 was subjected to high-temperature graphitization heat treatment at a temperature of 1600℃ and a holding time of 2.5h to obtain graphitized conductive carbon black (GC).

[0045] (2) Mix ammonium iodide and graphitized conductive carbon black obtained in step (1) in a mortar at a mass ratio of 1:25 for 40 min to obtain mixed powder. Place the mixed powder in a tube furnace, remove the air in the tube furnace, and heat-treat it in an inert atmosphere at a constant heating rate of 4℃ / min to 850℃ for 2 h to obtain iodine-doped carrier (I-GC).

[0046] (3) The iodine-doped support obtained in step (2) is dispersed with platinum nitrate at a mass ratio of 3:1 in a 30% water-70% ethanol solution and thoroughly stirred and mixed for 20 hours at a stirring rate of 300 rpm. It is then dried at 60°C and heat-treated in a tubular atmosphere furnace under 5% hydrogen / 95% argon conditions at 5°C / min to 170°C for 2 hours to obtain the fuel cell catalyst (Pt / I-GC).

[0047] Example 3

[0048] A method for preparing a fuel cell catalyst includes the following steps:

[0049] (1) Conductive carbon black Vulcan XC-72R was subjected to high-temperature graphitization heat treatment at a temperature of 1800℃ and a holding time of 3h to obtain graphitized conductive carbon black (GC).

[0050] (2) Mix ammonium iodide and graphitized conductive carbon black obtained in step (1) in a mortar at a mass ratio of 1:15 for 40 min to obtain mixed powder. Place the mixed powder in a tube furnace, remove the air in the tube furnace, and heat-treat it in an inert atmosphere at a constant heating rate of 3℃ / min to 800℃ for 2 h to obtain iodine-doped carrier (I-GC).

[0051] (3) The iodine-doped support obtained in step (2) is dispersed with platinum nitrate at a mass ratio of 4.5:1 in a 30% water-70% ethanol solution and thoroughly stirred and mixed for 20 hours. The mixture is dried at 60°C and then heat-treated in a tubular atmosphere furnace under 5% hydrogen / 95% argon conditions at 3°C / min to 180°C for 1.5 hours to obtain the fuel cell catalyst (Pt / I-GC).

[0052] Example 4

[0053] A method for preparing a fuel cell catalyst includes the following steps:

[0054] (1) Conductive carbon black Vulcan XC-72R was subjected to high-temperature graphitization heat treatment at a temperature of 1300℃ and a holding time of 5h to obtain graphitized conductive carbon black (GC).

[0055] (2) Mix ammonium iodide and graphitized conductive carbon black obtained in step (1) by grinding them in a mortar for 60 min at a mass ratio of 1:10 to obtain a mixed powder. Place the mixed powder in a tube furnace, remove the air from the tube furnace, and heat it in an inert atmosphere at a constant heating rate of 3℃ / min to 700℃ for 3 h to obtain an iodine-doped support (I-GC).

[0056] (3) The iodine-doped support obtained in step (2) is dispersed with platinum nitrate at a mass ratio of 2:1 in a 30% water-70% ethanol solution and thoroughly stirred and mixed for 12 hours at a stirring rate of 400 rpm. It is then dried at 60°C and heat-treated in a tubular atmosphere furnace under 5% hydrogen / 95% argon conditions at a temperature of 3°C / min to 120°C for 3 hours to obtain the fuel cell catalyst (Pt / I-GC).

[0057] Example 5

[0058] A method for preparing a fuel cell catalyst includes the following steps:

[0059] (1) Conductive carbon black Vulcan XC-72R was subjected to high-temperature graphitization heat treatment at a temperature of 2200℃ and a holding time of 2h to obtain graphitized conductive carbon black (GC).

[0060] (2) Mix ammonium iodide and graphitized conductive carbon black obtained in step (1) in a mortar at a mass ratio of 1:30 for 20 min to obtain mixed powder. Place the mixed powder in a tube furnace, remove the air in the tube furnace, and heat-treat it in an inert atmosphere at a constant heating rate of 3℃ / min to 1000℃ for 1 h to obtain iodine-doped carrier (I-GC).

[0061] (3) The iodine-doped support obtained in step (2) is dispersed with platinum nitrate at a mass ratio of 6:1 in a 30% water-70% ethanol solution and thoroughly stirred and mixed for 24 hours. The mixture is dried at 80°C and then heat-treated in a tubular atmosphere furnace under 5% hydrogen / 95% argon conditions at 3°C / min to 240°C for 3 hours to obtain the fuel cell catalyst (Pt / I-GC).

[0062] Comparative Example 1

[0063] A method for preparing a fuel cell catalyst includes the following steps:

[0064] (1) Conductive carbon black Vulcan XC-72R was subjected to high-temperature graphitization heat treatment at a temperature of 1800℃ and a holding time of 3h to obtain graphitized conductive carbon black (GC).

[0065] (2) The graphitized conductive carbon black obtained in step (1) and platinum nitrate were dispersed in a 30% water-70% ethanol solution at a mass ratio of 3.5:1 and thoroughly stirred and mixed for impregnation at a stirring rate of 300 rpm for 20 h. The mixture was dried at 60 °C and then heat-treated in a tubular atmosphere furnace under 5% hydrogen / 95% argon conditions at a temperature of 3 °C / min to 180 °C for 1.5 h to obtain the fuel cell catalyst (Pt / GC).

[0066] Comparative Example 2

[0067] A method for preparing a fuel cell catalyst includes the following steps:

[0068] (1) Conductive carbon black Vulcan XC-72R was subjected to high-temperature graphitization heat treatment at a temperature of 1800℃ and a holding time of 3h to obtain graphitized conductive carbon black (GC).

[0069] (2) Iodine and the graphitized conductive carbon black obtained in step (1) were mixed and stirred in a 30% water-70% ethanol solution at a mass ratio of 1:20 for 8 hours. After centrifugation and drying, the mixture was placed in a tube furnace. After removing the air from the tube furnace, the mixture was heated to 800℃ at a constant heating rate of 3℃ / min and then heat-treated in an inert atmosphere for 2 hours to obtain an iodine-doped support (I-GC).

[0070] (3) The iodine-doped support obtained in step (2) is dispersed with platinum nitrate at a mass ratio of 3.5:1 in a 30% water-70% ethanol solution and thoroughly stirred and mixed for 20 hours. The mixture is dried at 60°C and then heat-treated in a tubular atmosphere furnace under 5% hydrogen / 95% argon conditions at 3°C / min to 180°C for 1.5 hours to obtain the fuel cell catalyst (Pt / I-GC).

[0071] Comparative Example 3

[0072] A method for preparing a fuel cell catalyst includes the following steps: dispersing conductive carbon black Vulcan XC-72R and platinum nitrate in a 3.5:1 mass ratio in a 30% water-70% ethanol solution, stirring thoroughly to mix and impregnate the mixture at a stirring rate of 300 rpm for 20 h, drying at 60 °C, and heat-treating in a tubular atmosphere furnace under 5% hydrogen / 95% argon conditions at a temperature of 3 °C / min to 180 °C for 1.5 h to obtain the fuel cell catalyst.

[0073] Comparative Example 4

[0074] A method for preparing a fuel cell catalyst includes the following steps:

[0075] (1) Ammonium iodide and conductive carbon black Vulcan XC-72R were ground in a mortar at a mass ratio of 1:20 for 40 min to obtain a mixed powder. The mixed powder was placed in a tube furnace, and after the air in the tube furnace was removed, it was heated to 800℃ at a constant heating rate of 3℃ / min and then heat-treated in an inert atmosphere for 2 h to obtain an iodine-doped carrier.

[0076] (2) The iodine-doped support obtained in step (1) is dispersed with platinum nitrate at a mass ratio of 3.5:1 in a 30% water-70% ethanol solution and thoroughly stirred and mixed for 20 hours at a stirring rate of 300 rpm. It is then dried at 60°C and heat-treated in a tubular atmosphere furnace under 5% hydrogen / 95% argon conditions at a temperature of 3°C / min to 180°C for 1.5 hours to obtain the fuel cell catalyst.

[0077] Figure 1 This is a morphology image of the fuel cell catalyst in Example 1, from... Figure 1 As can be seen, the catalyst of the present invention exhibits obvious C lattice fringes of graphitized conductive carbon black, and the Pt particles are small in size and relatively uniformly distributed on the support.

[0078] The fuel cell catalysts of the examples and comparative examples were subjected to 5000 cycles of cyclic voltammetry scanning acceleration tests at scan rates of 1-1.5V and 0.5V / s. The test results are shown in Table 1 below. Figure 2 As shown.

[0079] Table 1. Performance test results of fuel cells fabricated in the examples and comparative examples.

[0080]

[0081]

[0082] As can be seen from Table 1, the catalyst of the present invention exhibits a small initial half-wave potential decay, indicating that the catalyst of the present invention has excellent stability and catalytic activity.

[0083] The catalyst in Comparative Example 1, lacking iodine doping, resulted in a decrease in half-wave potential. The catalyst in Comparative Example 2, employing a conventional mixed iodine doping method, was complex, and some iodine was unable to function due to its location within the catalyst (because oxygen could not reach the catalyst interior, whereas the iodine doping of this invention has high utilization), leading to a decrease in catalytic activity compared to the examples. In Comparative Example 3, the lack of graphitization treatment on the catalyst support and iodine doping resulted in significant half-wave potential decay and markedly poor catalyst stability. In Comparative Example 4, the lack of graphitization treatment on the conductive carbon black in the catalyst led to a high degree of oxidation and corrosion of the carbon support during accelerated cycling, causing Pt particle agglomeration or loss, and a significant decrease in performance.

[0084] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention and are not intended to limit the scope of protection of the present invention. Although the present invention has been described in detail with reference to preferred embodiments, those skilled in the art should understand that modifications or equivalent substitutions can be made to the technical solutions of the present invention without departing from the essence and scope of the technical solutions of the present invention.

Claims

1. A method for preparing a fuel cell catalyst, characterized in that, Includes the following steps: (1) Conductive carbon black is heat-treated to obtain graphitized conductive carbon black; the heat treatment temperature is 1300℃-2200℃; the heat treatment time is 2h-5h; (2) Mix ammonium iodide with the graphitized conductive carbon black obtained in step (1) to obtain a mixed powder, and then calcine the mixed powder to obtain an iodine-doped carrier; the calcination temperature is 700℃-1000℃ and the time is 1h-3h. (3) The iodine-doped support obtained in step (2) is impregnated in a platinum salt solution, dried, and heat-treated in a reducing atmosphere to obtain the fuel cell catalyst; the temperature of the heat treatment in the reducing atmosphere is 120℃-240℃, the time is 1h-3h, and the heating rate is 1℃ / min-5℃ / min.

2. The method for preparing a fuel cell catalyst according to claim 1, characterized in that, In step (2), the mass ratio of ammonium iodide to graphitized conductive carbon black is 1:(10-30).

3. The method for preparing a fuel cell catalyst according to claim 1, characterized in that, In step (3), the mass ratio of the iodine-doped carrier to the platinum salt is (2-6):

1.

4. The method for preparing a fuel cell catalyst according to claim 1, characterized in that, In step (3), the platinum salt includes platinum nitrate.

5. The method for preparing a fuel cell catalyst according to claim 1, characterized in that, In step (3), the reducing atmosphere is a mixture of hydrogen and argon; and / or, the solvent for the platinum salt solution is water and ethanol.

6. The method for preparing a fuel cell catalyst according to any one of claims 1 to 5, characterized in that, In step (2), the heating rate of the calcination is 2℃ / min-6℃ / min; and / or, the calcination is carried out in an inert atmosphere.

7. A fuel cell catalyst prepared by the method of any one of claims 1-6.

Citation Information

Patent Citations

  • Graphitized carbon loaded platinum-based catalyst and preparation method thereof

    CN119381468A

  • Preparation method for nano platinum / carbon electric catalyst for polymer electrolyte membrane fuel cell cathode

    CN1380711A